Ankylosing spondylitis and pregnancy: a current view on the problem - O. A. Krichevskaya; Z. M. Gandaloeva; Т. V. Dubinina (Современная ревматология, 2018)
Ankylosing spondylitis (AS) more often develops in the 3rd and 4th decade of life when many women think about motherhood. Today, the view which has prevailed since the middle of the 20th century on AS as a male disease has been revised; the male to female ratio for this disease is approaching 1:1, which makes it urgent to study the problem of pregnancy in AS. The review gives the data available in the literature on fertility in AS, the interaction of the latter and pregnancy, and drug therapy during gestation. There is evidence for further investigations to clarify the course of AS, to optimize the assessment of its activity and patients' functional status, to identify markers for an exacerbation of the disease during pregnancy and after childbirth, and to standardize drug therapy when preparing for pregnancy and during the latter.